Spontaneous ping-pong fracture in a full-term neonate-a case report - Walid Alhussin; Sukena Susnerwala (SpringerOpen, 2023)
Abstract Background Non-traumatic depressed skull fracture in a neonate delivered by cesarean section is a rare phenomenon. The incidence reported in literature varies between 1 and 2.5 in every 10,000 live births. The skull is transformed from its normal convex shape to a more concave form due to easy malleability. This is secondary to the lack of complete ossification in the neonatal period. Hence, it is commonly known as ping-pong fracture. The clinical presentation may vary depending on the severity of the fracture and underlying parenchymal injury. Most cases reported in literature have been managed conservatively. However, surgical elevation and the use of medical devices may be advised in severe cases. Case presentation We report the presentation, course, and management of a term female neonate with a spontaneous ping-pong fracture. The neonate had no history suggestive of antenatal insult, difficult labor, or trauma due to instrumentation during delivery. The infant was thoroughly investigated for underlying parenchymal injury, observed for neurological abnormality, and managed conservatively. Conclusion Thus, ping-pong fractures or spontaneous neonatal skull fractures are rare but can be encountered in clinical practice. A thorough clinical examination and neurological assessment can aid management decisions.